Letter (copy) : Spanish Republicans in France - Tewson, Vincent
035-0073-001 International. HVT/EAB/DT/1340. 15th June, 1945 Mr. T. Buller, Amalgamated Engineering Union, 28, Hallam Road, Mapperley. NOTTINGHAM Dear Mr. Buller, SPANISH REPUBLICANS IN FRANCE. Further to my letter of 12th June, we have now made enquiries from the International Federation of Trade Unions who have a continuous record of assisting Spanish refugees, and they are actually in the course of examining means by which they can make the best possible use of monies they have available. I have, there, passed the money collected by your Council to the I.F.T.U. to be placed in its International Solidarity Fund. The official receipt of the I.F.T.U. is enclosed herewith. Yours sincerely, Assistant Secretary. Receipt. 292/946/35/73